Ethical Challenges in Intercultural Citizenship Education with ‘Difficult Topics’ in the World Language Classroom and Beyond - Porto, Melina (2025)
The purpose of this article is to examine the ethical challenges that arise in the world language classroom and beyond from using intercultural citizenship pedagogy. Intercultural citizenship is, in general, seen as a recent and positive development in intercultural language education for helping students engage with topics of social significance in the classroom. However, there are ethical challenges involved, for instance, related to the political or sensitive nature of such topics. We define and illustrate some of these ethical concerns and their implications for education by drawing on an intercultural citizenship project about COVID-19 carried out in two higher education contexts in 2020. The analysis of this example shows that these ethical concerns are unavoidable but can be minimised with an action research perspective and a combination of pedagogies of intercultural citizenship, discomfort, and the arts. We conclude with a discussion of the transferability of the example and its consequences for any language and intercultural communication teaching which deals with controversial and sensitive matters.